INTERRUPCIÓN DE GESTACIÓN EN PERRAS UTILIZANDO DEXAMETASONA ORAL - Sánchez R., Alfonso (2006)
The purpose of this study was to describe reproductive and clinical parameters as a result of dexamethasone administration in order to terminate unwanted pregnancy in bitches. Five pregnant adult bitches, clinically healthy, were used. Animals were orally administered 0.2 mg/kg of dexamethasone every 12 hours during 6 days and thereafter, the dose was gradually reduced till 0.02 mg/kg on day 10. Ultrasound scan, body temperature, plasma progesterone, and behaviour were recorded throughout the study. The gestation was satisfactorily interrupted in 4 out of 5 bitches, where absorption or abortion occurred between 7 to 16 days after the beginning of the treatment. In the remaining animal, the interruption was partial (absorption and birth of immature puppies). Body temperature felt 1.0 - 1.5 ºC prior to the absorption or abortion. Progesterone concentration descended at day 4 of treatment and absorption or abortion occurred after progesterone declined to <1 ng/ml. A greenish discharge was observed in abortions. The more frequent side-effects observed were polydipsia and polyuria, whereas vomiting and anorexia was observed in smaller proportion. The administration of dexamethasone would have a similar effect to the liberation of fetal cortisol in the normal mechanism of the parturition and therefore, it would be a medical alternative for the control of canine overpopulation, particularly in those cases of unwanted pregnancy.